2020
DOI: 10.1021/acsabm.0c01384
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Enhanced NIR-IIb Emission of Indocyanine Green for Functional Bioimaging

Abstract: Fluorescence imaging performed in the 1500−1700 nm spectral range (labeled near-infrared IIb, NIR-IIb) promises high imaging contrast and spatial resolution for its little photon scattering effect and minimum autofluorescence. Though inorganic and organic probes have been developed for NIR-IIb bioimaging, most are in the preclinical stage, hampering further clinical application. Herein, we showed that indocyanine green (ICG), a US Food and Drug Administration (FDA)-approved agent, exhibited a remarkable amount… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The synthesis routes of BBTD-BTE and BBTD-BTE-PEG are presented in Scheme 1. BBTD-BTE was prepared by the Suzuki reaction between 1,2-bis(5-chloro-2-methylthiophen-3yl)cyclopent-1-ene (BTE) and 4,8-dibromobenzo[1,2-c;4,5-c′]bis [1,2,5]thiadiazole (BBTD), and the two flanking aryl chlorides in BBTD-BTE were further used to incorporate poly(ethylene glycol) (PEG) chains to achieve hydrophilic modification. The characterization data of the intermediates and target compound can be found in Figures 1 and S1−S13.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis routes of BBTD-BTE and BBTD-BTE-PEG are presented in Scheme 1. BBTD-BTE was prepared by the Suzuki reaction between 1,2-bis(5-chloro-2-methylthiophen-3yl)cyclopent-1-ene (BTE) and 4,8-dibromobenzo[1,2-c;4,5-c′]bis [1,2,5]thiadiazole (BBTD), and the two flanking aryl chlorides in BBTD-BTE were further used to incorporate poly(ethylene glycol) (PEG) chains to achieve hydrophilic modification. The characterization data of the intermediates and target compound can be found in Figures 1 and S1−S13.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In recent years, the emergence of various optical functional materials has been greatly accelerating the development of optical imaging and therapy . In the context of optical imaging, the fluorescence (FL) imaging in the second near-infrared (NIR-II) window presents great advantages compared to the visible and traditional near-infrared (NIR-I) fluorescence imaging in terms of imaging resolution, depth, and signal-to-noise ratio due to the lower tissue scattering and absorption and depressed autofluorescence in the NIR-II optical window. As contrast agents, NIR-II fluorophores determine the quality of the fluorescence imaging. Because the excited-state energy can be relaxed by both radiative and nonradiative decay pathways, apart from photoluminescence, NIR-II fluorophores generally possess photothermal-related functionalities, such as photoacoustic (PA) imaging and photothermal therapy (PTT). Moreover, most NIR-II fluorophores have NIR absorption, which would further impart high performance to PA imaging and PTT thanks to the high tissue penetration of the NIR light . Compared to fluorescence imaging, the PA technique has its intrinsic advantages; for example, it has a higher imaging depth and can achieve tomographic imaging and 3D reconstruction, providing more medical information. However, PA imaging has relatively lower sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In plasma, the absorption and emission peaks of ICG are around 807 and 822 nm (Schaafsma et al, 2011). Furthermore, the fluorescent intensity increases when ICG is mixed with fetal bovine serum (FBS) or human serum albumin (HSA) (He et al, 2020), and the quantum yield has been shown to increase by nearly 3.5 times when it is mixed with FBS (Jung et al, 2013). Mordon et al (1998) suggested that, in plasma, some ICG binds to blood endothelial cells, further increasing the maximum absorbance wavelength from 826 to 835 nm, but it is unknown if the same process occurs in lymphatic vessels.…”
Section: Dendrimersmentioning
confidence: 99%
“…Although ICG has an emission spectra peak in the NIR-I range, it displays a long tail that can be detected in the NIR-II and SWIR ranges using appropriate sensors. The potential benefit of doing this is the lower tissue autofluorescence and scattering, giving improved SBR, contrast, and spatial resolution, and although other NIR-II/SWIR fluorophores exist, ICG is FDA-approved (He et al, 2020;Swamy et al, 2021). Carr et al (2018) used 808 nm excitation light and an indium gallium arsenide (InGaAs) SWIR sensor (NIRvana 640, Princeton Instruments) with 1,000-1,400 nm long-pass filters to interrogate ICG after subcutaneous injection in mice hind feet and tails.…”
Section: Extended Wavelengthsmentioning
confidence: 99%
See 1 more Smart Citation